Using Adele’s “Someone Like You” to Teach Verbs Tenses and Passive Forms - Ariya Jati (PAROLE: Journal of Linguistics and Education, 2013)
This  paper  is  about  how  to  use  Adele’s  “Someone  Like  You”  to teach tenses and passive forms. Adele’s song lyric was potentially used  in  an  English-as-a  Foreign  Language  (EFL)  classroom.  This study is to provide a practical alternative to the teaching of tenses and  passive  forms. The  teaching  is  performed  in  three  phases namely text  completion, verb  categorization, and  sentence construction. The teaching is expected the students to demonstrate their  receptive  and  productive  skills in  English  language  by  using the lyric. (By such a teaching, the students are expected to be able to demonstrate  their  receptive  and  productive  skills  in  English language by using the lyric.)Makalah ini tentang penggunaan lirik “Someone Like You” karya Adele untuk mengajarkan kala dan bentuk pasif. Lirik lagu Adele tersebut  dapat  digunakan  di  dalam    kelas  dengan  bahasa  Inggris sebagai  bahasa  asing. Kajian  ini  untuk  memberikan  alternatif praktis  bagi  pengajaran  kala    dan  bentuk  pasif  bagi  mahasiswa EFL. Pengajaran dilakukan dalam tiga tahap, yaitu: pengisian teks, kategorisasi  kata  kerja, dan  penyusunan kalimat.  Pengajaran  ini diharapkan  dapat  memungkinkan  mahasiswa  menampilkan keterampilan  reseptif  dan  produktif  mereka  dalam  berbahasa Inggris melalui lirik tersebut.